AGE-RAGE axis culminates into multiple pathogenic processes: a central road to neurodegeneration - Bhattacharya, Reshmee; Alam, Mohammad Rizwan; Kamal, Mohammad Azhar; Seo, Kyung Jin; Singh, Laishram Rajendrakumar (Frontiers in Molecular Neuroscience, 2023)
Advanced glycation end-products (AGEs; e.g., glyoxal, methylglyoxal or carboxymethyl-lysine) are heterogenous group of toxic compounds synthesized in the body through both exogenous and endogenous pathways. AGEs are known to covalently modify proteins bringing about loss of functional alteration in the proteins. AGEs also interact with their receptor, receptor for AGE (RAGE) and such interactions influence different biological processes including oxidative stress and apoptosis. Previously, AGE-RAGE axis has long been considered to be the maligning factor for various human diseases including, diabetes, obesity, cardiovascular, aging, etc. Recent developments have revealed the involvement of AGE-RAGE axis in different pathological consequences associated with the onset of neurodegeneration including, disruption of blood brain barrier, neuroinflammation, remodeling of extracellular matrix, dysregulation of polyol pathway and antioxidant enzymes, etc. In the present article, we attempted to describe a new avenue that AGE-RAGE axis culminates to different pathological consequences in brain and therefore, is a central instigating component to several neurodegenerative diseases (NGDs). We also invoke that specific inhibitors of TIR domains of TLR or RAGE receptors are crucial molecules for the therapeutic intervention of NGDs. Clinical perspectives have also been appropriately discussed.